3D Hierarchical Indium Tin Oxide Nanotrees for Enhancement of Light Extraction in GaN‐Based Light‐Emitting Diodes. Issue 2 (15th November 2016) - Park, Min Joo; Kim, Chan Ul; Kang, Sung Bum; Won, Sang Hyuk; Kwak, Joon Seop; Kim, Chil‐Min; Choi, Kyoung Jin
Abstract : Recently, 3D nanostructures have attracted much interest because of their interesting electrical/optical properties such as wave guiding modes, light scattering, antireflection effects, etc. In this work, a facile yet efficient method for the fabrication of hierarchical 3D indium tin oxide (ITO) nanotrees (NTs) and their integration in GaN‐based blue‐light‐emitting diodes (LEDs) for efficient light‐extraction are reported. The ITO NTs are fabricated by the oblique‐angle (≈85°) deposition method at 240 °C using electron‐beam evaporation. The ITO NTs grow via a self‐catalytic vapor–liquid–solid mechanism with the branches having an epitaxial relationship with the trunks. The ITO NTs successively deposited on an ITO thin film as a p‐contact layer are annealed at 600 °C for 1 min under ambient air in order to form a transparent ohmic contact. The indium gallium nitrde/gallium nitride (InGaN/GaN) LED with ITO NTs presents a 29.5% enhancement in the light output power at an injection current of 20 mA, compared to the reference LED with an ITO thin film p‐contact. This enhancement is ascribed to the effective light extraction of the ITO NTs due to to the gradually decreasing profile of the refractive index from 2.08 (ITO thin film), 1.15 (dense ITO NTs), 1.06 (porous ITO NTs) to 1.0 (air). These results are in good agreement with the optical simulation by the COMSOL wave optics module. Abstract : A facile yet efficient method for the fabrication of hierarchical 3D indium tin oxide (ITO) nanotrees (NTs) and their integration in GaN‐based blue‐light‐emitting diodes (LEDs) for efficient light‐extraction are reported. The InGaN/GaN LED with ITO NTs presents 29.5% enhancement in the light output power at an injection current of 20 mA.